MODALITAS KALIMAT PADA ANTOLOGI CERITA PENDEK LUKISAN KALIGRAFI KARYA A. MUSTOFA BISRI - Imeylda Afyolanda; Anita Widjajanti; Furoidatul Husniah (Universitas Negeri Makassar, 2018)
Modality Sentence in Short Story Anthology Lukisan Kaligrafi By A. Mustofa Bisri. The aim of this research is to describe about modality sentence as a way to uncover A. Mustofa Bisri's style in short story anthology Lukisan Kaligrafi. This research uses descriptive qualitative research design. The results of this research are the types of modalities including intensional modality, epistemic modality, dynamic modality, and deontic modality. The functionality of modalities includes the function of changing the tone, expressing attitudes, and mood expression. Furthermore, modality as a learning alternative of short story text material for SMA class XI that focuses on characterizing short stories.